Characterization of cysteine dioxygenase in the liver of bluegill Lepomis macrochirus for the determination of enzyme activity - Onoda, Kan; Goto, Takanobu; Kobayashi, Tarou; Imai, Keiko; Yamamoto, Syogo; Ooya, Kotarou (Aquaculture Science, 2021)
We studied the characterization of cysteine dioxygenase (CDO) in the liver of bluegill Lepomis macrochirus. The content of cysteinesulfinic acid (CSA) produced by enzymic reaction was determined by means of OPA-prelabeling and reverse-phase HPLC using homocysteic acid (HCA) as an internal standard. Production of CSA from cysteine was elevated when the liver homogenate was incubated with increases in reaction time and concentration of protein and cysteine, respectively. The CSA production reached maximum velocity when the incubation was conducted at pH of 6.1 and temperature of 27°C. At the same pH, phosphate buffer resulted in higher CSA formation than 2-morpholinoethanesulfonate buffer. As demonstrated in mammals, an addition of hydroxylamine into the reaction mixture was needed for CSA formation but the higher concentration of this amine decreased the amino acid production. Same phenomenon was observed in the case of ferrous ion added into the reaction mixture. Neither NAD+ nor bathocuproinedisulfonic acid exhibited any significant effects on the CSA production in bluegill homogenate. Our present data indicated a conclusion that the characterization of CDO in the liver of bluegill was basically similar to those in mammals but the enzyme in this fish is sensitive to chemicals and temperature than that in mammals.